2021
DOI: 10.1002/ppul.25520
|View full text |Cite
|
Sign up to set email alerts
|

High burden of acquired morbidity in survivors of pediatric acute respiratory distress syndrome

Abstract: Introduction: With improving mortality rates in pediatric acute respiratory distress syndrome (PARDS), functional outcomes in survivors are increasingly important. We aim to describe the change in functional status score (FSS) from baseline to discharge and to identify risk factors associated with poor functional outcomes.Methods: We examined clinical records of patients with PARDS admitted to our pediatric intensive care unit (PICU) from 2009 to 2016. Our primary outcome was acquired morbidity at PICU and hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Recent studies demonstrated impairments in HRQL (20, 23–25), functional status (23–30), neurocognitive status (31, 32), emotional health (24), and school participation (18, 33) in the months and years after hospitalization with PARDS, as well as high rates of ongoing care needs after hospital discharge (28, 29, 34), postdischarge health resource use (14, 17, 19), late mortality (14, 18, 23, 31, 35, 36), and work absences for parents (33) ( Table 2 ) (Supplemental Table 9, http://links.lww.com/PCC/C297).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies demonstrated impairments in HRQL (20, 23–25), functional status (23–30), neurocognitive status (31, 32), emotional health (24), and school participation (18, 33) in the months and years after hospitalization with PARDS, as well as high rates of ongoing care needs after hospital discharge (28, 29, 34), postdischarge health resource use (14, 17, 19), late mortality (14, 18, 23, 31, 35, 36), and work absences for parents (33) ( Table 2 ) (Supplemental Table 9, http://links.lww.com/PCC/C297).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of pediatric trauma patients with PARDS, 77.1% of were discharged with an abnormal Functional Independence Measure (37) score compared with 30.7% of trauma patients without PARDS (29), and 9.4% of these trauma patients with acute respiratory failure had a decline in POPC at discharge (26). In two cohorts of general PICU patients with PARDS, 16–23% experienced new morbidity at hospital discharge based on increase in Functional Status Scale (FSS) (38) score by greater than or equal to 3 points (28, 30) with 39% experiencing any FSS increase, primarily manifested by 28% requiring new feeding support and 11% requiring new respiratory support (30). Following discharge, 31% of PARDS patients had a new morbidity defined by FSS increase greater than or equal to 3 points at 3 months post admission relative to preillness baseline, and 23% had new morbidity at 9 months (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is variability in mortality rates and availability of ECMO for pediatric ARDS across the world, there is increasing focus on longer-term functional outcomes in both pediatric ARDS (10)(11)(12) and pediatric ECMO survivors (13)(14)(15). This is an important consideration in the context of factors that determine ECMO candidacy.…”
Section: Discussionmentioning
confidence: 99%
“…The change in the FSS scores from admission to discharge (ΔFSS) in patients with ARDS was 12 (-9, 17), indicating the presence of functional deterioration during the ICU stay. A previous study found that the median baseline FSS score in patients with pediatric ARDS (PARDS) treated with ECMO increased to 11 ( 8 , 12 ) at PICU discharge ( 17 ). Cashen et al reported that 29% of patients with PARDS treated with ECMO had moderate (FSS score of 10–15) and severe abnormal functional status (FSS score of 16–21) at hospital discharge ( 18 ).…”
Section: Discussionmentioning
confidence: 99%